Genome‐wide identification of long non‐coding RNAs (lncRNAs) associated with malathion resistance in Bactrocera dorsalis. Issue 5 (28th January 2021) - Meng, Li‐Wei; Yuan, Guo‐Rui; Chen, Meng‐Ling; Dou, Wei; Jing, Tian‐Xing; Zheng, Li‐Sha; Peng, Meng‐Lan; Bai, Wen‐Jie; Wang, Jin‐Jun
Abstract: BACKGROUND: Long non‐coding RNAs (lncRNAs) play important roles in the regulation of biological processes and have been identified in many species including insects. However, the association between lncRNAs and pesticide resistance in insect species such as Bactrocera dorsalis is unknown. RESULTS: RNA‐seq was performed on malathion resistant (MR1) and susceptible (MS) strains of B. dorsalis and a total of 6171 lncRNAs transcripts were identified. These included 3728 lincRNAs, 653 antisense lncRNAs, 1402 intronic lncRNAs, and 388 sense lncRNAs. A total of 40 and 52 upregulated lncRNAs were found in females and males of the MR1 strain compared to 54 and 49 in the same sexes of the MS strain, respectively. Twenty‐seven of these lncRNAs showed the same trend of expression in both females and males in the MR1 strain, in which 15 lncRNAs were upregulated and 12 were downregulated. RT‐qPCR results indicated that the differentially expressed lncRNAs were associated with malathion resistance. The lnc15010.10 and lnc3774.2 were highly expressed in the cuticle of the MR1 strain, indicating that these two lncRNAs may be related to malathion resistance. RNAi of lnc3774.2 and a bioassay showed that malathion resistance was possibly influenced by changes in the B. dorsalis cuticle. CONCLUSION: LncRNAs of B. dorsalis potentially related to the malathion resistance were identified. Two lncRNAs appear to influence malathion resistance via modulating the structure, or components, of the cuticle. © 2021 Society of Chemical Industry Abstract : ( 1) The 6, 171 long non‐coding RNAs of Bactrocera dorsalis were first identified in genome‐wide. (2) lnc3774.2 and lnc15010.10 might participated in malathion resistance of B. dorsalis via modulate cuticle.